Genetic diversity among flue-cured tobacco cultivars on the basis of AFLP markers - Xiao Zhen Liu; Chuan Shen He; Yu Ming Yang; Han Yao Zhang (Czech Journal of Genetics and Plant Breeding, 2009)
AFLP analyses were used to assess the genetic similarity among selected accessions at the South China Tobacco Breeding Research Centre (Yunnan province, Southwest China). 154 AFLP polymorphic fragments out of 561 fragments were used to assess the genetic diversity among 28 tobacco accessions. The average number of polymorphic bands per AFLP primer pair was 15.4. AFLPs seemed to be an effective classification tools for germplasm conservation and breeding. Limited genetic variation was detected within this group of accessions. The relationship of cultivars was estimated by cluster analysis based on AFLP data.